Possible Role of Autoimmunity in Patients with Premature Ovarian Insufficiency - Renata Košir Pogačnik; Helena Meden Vrtovec; Alenka Vizjak; Alenka Uršula Levičnik; Nina Slabe; Alojz Ihan (International Journal of Fertility and Sterility, 2014)
Background: To evaluate the involvement of immune abnormality in patients with idiopathic premature ovarian insufficiency (POI). In addition to the known etiology, autoimmune disorders may be a pathologic mechanism for POI. Materials and Methods: Our study was a prospective controlled trial. Twenty women with POI, reasons other than autoimmune excluded, were enrolled in this study. The control group consisted of 17 healthy women. In both groups, family and personal history were taken and the levels of follicle stimulating hormone, luteinizing hormone, thyroid-stimulating hormone, prolactin, anti-Müllerian hormone, inhibin B, antithyroglobulin and antithyroid peroxidase antibodies were determined. Antiovarian antibodies and subpopulations of peripheral blood T-lymhocytes were also determined. Results: Participants in the study group exhibited hypergonadotropichypogonadism, while high levels of follicle stimulating hormone and low levels of inhibin B and anti-Müllerian hormone were observed. In 16 (80%) patients, POI was associated in their personal and familial history with another autoimmune disease. Fifty percent of patients presented highly elevated antithyroid antibodies. The lymphocyte subset, especially B cells, was significantly higher (p=0.014), and peripheral regulatory lymphocytes CD25+ high were significantly lower (p=0.015) in the study group than in the control group. Anti- ovarian antibodies were detected in 20% of patients with POI. Conclusion: We presume that the presence of anti-ovarian antibodies together with abnormalities of cellular immunity may in some cases potentially represent the involvement of an autoimmune mechanism in idiopathic POI.